Comparing Seroprotective Levels of IgG Antibody Against Single and Two Shots of Measles-Rubella-Mumps (MMR) Vaccine in Children Aged 12 Months to 15 Years Old in Southern Iran, Ahvaz in 2018 - Nashibi, Roohangiz; Ahmadi, Fatemeh; Keshvadi, Ghazaleh; Keshvadi, Mohammad Hosein (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Background and Objective: Despite inclusive measles and rubella vaccination programs, the epidemics are still present in some areas. The present study aimed to evaluate the efficacy of these two vaccines simultaneously by testing the levels of IgG antibodies in children aged 12 months to 15 years old in Southern Iran. Methods: This was a cross-sectional study on serum blood samples of 400 children aged 12 months to 15 years old in Ahvaz, Southern Iran in 2018. The children were divided into the following age groups: age group of 12 months to 17 months and 29 days who received a single dose of Measles, Rubella, Mumps (MMR) vaccine; age group of 18 months to 10 years old who received two doses of MMR vaccine at the ages of 12 months and 18 months; and age group of 11 to 15 years old who received two doses of MMR vaccine at the age of 12 months and 4-6 years old. In the assessments, the protective levels were defined as per the guidelines of the ELISA kit (VIRCELL Co., Spain) as follows: The serum IgG antibody levels above 11 IU/ml were defined as positive protective level, 9 to 11 IU/ml as an equivalent state, and the serum antibody level below 9 IU/ml as a negative state. Accordingly, the equivalent and negative cases were reported as negative and cases above 11 IU/ml were positive. Results: The male to female ratio was 1.02. Most of the patients (69%) were in the age group 18 months to 10 years old. In all age groups, the number of people with a high serum anti-rubella and anti-measles IgG antibody level was higher than the protective level. There was no significant difference between the mean serum anti-rubella and anti-measles IgG antibody level between the age groups (P= 0.515, P= 0.176, respectively). For rubella, 86.66% of females and 83.16% of males, and for measles, 86.36% of females and 83.66% of males were seropositive, and there was no significant difference by two sexes (P= 0.486 and P= 0.412, respectively). Conclusions: The frequency of seropositive anti-measles and anti-rubella vaccine was not significantly different between the subjects with a single dose and those with two doses of MMR vaccine. Further studies are needed to evaluate the adequacy of the MMR vaccine for Iranian children. Moreover, due to the lower average serum IgG antibody level measles and rubella in males, further investigation is needed to find out the causal relationship between the lack of appropriate response to vaccine injection and male gender.